π-Allylpalladium Complexes in Synthesis: An Update - Parisotto, Stefano; Deagostino, Annamaria (Synthesis, 2019)
This review aims to summarize the development of the chemistry of π-allylpalladium complexes both as intermediates and catalysts/reagents between 2013 and early 2109. Major attention has been devoted to the synthetic aspect of these versatile intermediates.1 Introduction2 π-Allylpalladium Complexes Generated from Allyl Electrophiles2.1 Activated Allylic Compounds2.2 Unactivated Allylic Compounds: Allylic Alcohols and Hydrocarbons2.3 Total Syntheses3 π-Allylpalladium Complexes Generated from Dienes3.1 Conjugated Dienes3.2 Allenes4 π-Allylpalladium Complexes Exploited as Reactants and Precatalysts4.1 Allylpalladium-Catalyzed Dehydrogenation4.2 Allylpalladium-Catalyzed Synthesis of Alkenylboronic Esters4.3 Allylpalladium-Based Precatalysts5 Conclusions
Keywords: palladium; allyl; Tsuji–Trost; dienes; enantioselective synthesis; palladium precatalyst